2022
DOI: 10.1021/acs.energyfuels.2c01848
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Angstrom-Scale Pore Structure in Organic-Rich Shales by Using Low-Pressure CO2 Adsorption and Multifractal Theory and Its Role in CH4/CO2 Gas Storage

Abstract: Knowledge of CH 4 and CO 2 storage in pore systems of organic-rich shale can provide valuable perspectives on gasbearing properties and CO 2 sequestration in shale reservoirs. To finely characterize the angstrom-scale pores and investigate their role in CH 4 /CO 2 storage behaviors, this study examines 14 Lower Cambrian Niutitang shale samples by using an array of experiments, including total organic carbon (TOC) content tests, optical observations, section analysis, X-ray diffraction analysis, fieldemission s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…It also reveals a good correlation range from 27 to 80%. Li et al 91 revealed a relationship between pore structure characteristics and mineral contents. It shows a positive correlation between the pore attributes and the TOC content, while it shows a negative correlation between the pore attributes and the clay content.…”
Section: Discussionmentioning
confidence: 99%
“…It also reveals a good correlation range from 27 to 80%. Li et al 91 revealed a relationship between pore structure characteristics and mineral contents. It shows a positive correlation between the pore attributes and the TOC content, while it shows a negative correlation between the pore attributes and the clay content.…”
Section: Discussionmentioning
confidence: 99%
“…For the measurement consistent with multifractal distribution, the number of boxes with similar α values, which here will be called N α (ε), satisfies the exponential function with ε N α ( ε ) ε f ( α ) where f (α) represents the fractal dimensions of a set of points with singularity α.…”
Section: Methodsmentioning
confidence: 99%